Arbuscular mycorrhizal fungi affect the concentration and distribution of nutrients in the grain differently in barley compared with wheat - Stephanie J. Watts‐Williams (Plants, People, Planet, 2021)
Societal Impact Statement Cereal crops such as wheat and barley provide key nutritional elements to the human diet. However, the distribution of nutrients within the cereal grain itself is critically important, as nutrients can be lost during the grain milling process. Mycorrhizal fungi can take up nutrients from the soil and deliver them to plants, and consequently, grain nutrient content can be modified by inoculation of the soil with mycorrhizal fungi. Here we show at the microscopic level how mycorrhizal fungi modify the concentration and distribution of nutrients within wheat and barley grain, and consider the impact of this for human nutrition. Summary The concentration and distribution of nutrients in cereal grains are critically important for human nutrition. Mycorrhizal fungi affect the yield and nutrition of cereal crops, but there has been little focus on the effects on the grain, particularly at the microscopic level. Although arbuscular mycorrhizal fungi (AMF) can modify grain nutrient concentrations relative to mock‐inoculated plants, it is not known whether this contributes to modifications to the distribution of nutrients within the grain. Barley and bread wheat plants were grown to maturity with or without AMF (Rhizophagus irregularis) inoculation in soil amended with 20 mg added zinc kg−1. The resulting grain from matured plants was dried, fixed and sectioned to the root primordia level, then subjected to laser ablation ICP‐MS to analyse the distribution and concentration of 12 elements. Elemental concentration and localisation in the grain samples was highly influenced by plant species, and for some elements, AMF inoculation. Heavy metals (zinc, iron, manganese, copper, cobalt and nickel) were the most highly influenced by AMF inoculation, particularly in wheat; macronutrients including phosphorus, magnesium, potassium and sulphur were also affected by AMF, particularly in barley. Elemental concentrations, particularly of macronutrients, tended to be greater in mycorrhizal barley grain than non‐mycorrhizal, but the reverse was observed in wheat grain. Mycorrhizal plants of both species had reduced accumulation of manganese, nickel and cobalt in the grain.